Exploring Differences in Teaching Methods and Classroom Management Between Novice and Experienced Teachers - Marta Afrida Sampurna; Luh Putu Artini; Ni Luh Putu Eka Sulistia Dewi (English Education Department STKIP Agama Hindu Singaraja, 2025)
The objective was to examine and contrast the teaching practices of novice and experienced teachers, focusing on affective strategies, classroom structure, feedback, content enrichment, and cooperative learning. A qualitative observational method was employed to analyze classroom behaviors, assessment techniques, and student interactions. Data were gathered from multiple sessions conducted by teachers at different career stages, allowing for in-depth comparison. Findings revealed that novice teachers prioritize creating supportive, emotionally engaging, and interactive environments, while experienced teachers tend to adopt more structured, discipline-focused, and academically rigorous methods. Feedback strategies also differed, with novices using collaborative assessments and experienced teachers favoring teacher-led correction. Differences were influenced by factors such as teaching experience, pedagogical confidence, professional development, and institutional expectations. In conclusion, the study underscores the evolving nature of teaching practices, highlighting the need for targeted professional development and mentorship programs to support novice teachers in transitioning toward experienced, effective instructional methods.